Elucidation of Callistemon lanceolatus-derived natural compounds in STAT 3 pathway against human cancer cells: in silico and in vitro studies - Zafar, Mubashir; Anwar, Sadaf; Hussain, Malik Asif; Iqbal, Naveed; Ali, Abrar; Sadaf,; Najm, Mohammad Zeeshan; Kausar, Mohd Adnan (Frontiers in Pharmacology, 2025)
IntroductionMany human tumours have hyperactive signal transducer and activator of transcription 3 (STAT3, positioning it as a prime target for natural compounds with anticancer properties. This study investigated three small-molecule STAT3 inhibitors derived from Callistemon lanceolatus: cyanidin-3,5-diglucoside, kaempferol-3-o-β-d-galactopyranoside, and quercetin-3-o-(2″-o-galloyl)-β-d-galactopyranoside.Material and methodsThe compounds were explored through virtual screening and molecular dynamics (MD) simulations to understand the intracellular processing of activated STAT3. The biological effects of these STAT3 inhibitors on human cancer cells were assessed via simulation. Further, in-vitro studies were performed to exhibit the anti-cancer role of compounds on cancer cell lines.Results and discussionIt is revealed through results that active components in these compounds inhibited cancer cell migration and invasion and suppressed the proliferation of noncancer cells. Moreover, these natural compounds from C. lanceolatus downregulated the expression of STAT3 downstream target proteins, indicating their potential as therapeutic agents against cancer. Thus, cyanidin-3,5-diglucoside, kaempferol-3-o-β-d-galactopyranoside, and quercetin-3-o-(2″-o-galloyl)-β-d-galactopyranoside from C. lanceolatus are promising candidates for cancer treatment.